Felt Sensing of Speech Acts in Written Genre Acquisition - Randall Popken (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
This paper theorizes about the experiential dimension of acquiring rhetorical genres—specifically the way developing writers rely on felt sensing when they encounter the "core" of genres: illocutionary speech acts.